Methoxy-substituted tetrakisquinoline analogs of EGTA and BAPTA for fluorescence detection of Cd2+ 1. Issue 12 (30th January 2019) - Mikata, Yuji; Kaneda, Minori; Konno, Hideo; Matsumoto, Arimasa; Sato, Shin-ichiro; Kawamura, Masaya; Iwatsuki, Satoshi
Abstract : A 5, 6, 7-trimethoxyquinoline-based octadentate ligand with a BAPTA (1, 2-bis(2-aminophenoxy)ethane- N, N, N ′, N ′-tetraacetic acid) structure exhibits Cd 2+ -specific fluorescence enhancement. Abstract : EGTA (ethylene glycol bis(2-aminoethyl ether)- N, N, N ′, N ′-tetraacetic acid) and BAPTA (1, 2-bis(2-aminophenoxy)ethane- N, N, N ′, N ′-tetraacetic acid) are well-known Ca 2+ chelators that have four carboxylates, two nitrogen atoms and two ether oxygen atoms. In the present study, we prepared EGTQ ( N, N, N ′, N ′-tetrakis(2-quinolylmethyl)-1, 2-bis(2-aminoethoxy)ethane) and BAPTQ ( N, N, N ′, N ′-tetrakis(2-quinolylmethyl)-1, 2-bis(2-aminophenoxy)ethane) as quinoline alternatives of EGTA and BAPTA, respectively. In methanol–HEPES buffer solution (9 : 1, 50 mM HEPES, 0.1 M KCl, pH = 7.5), EGTQ exhibits fluorescence enhancement induced by Zn 2+ and Cd 2+ with poor selectivity, but BAPTQ did not exhibit a fluorescence response to either metal ion. Introduction of three methoxy substituents at the 5, 6, 7-positions of each quinoline moiety in BAPTQ specifically enhanced the fluorescence intensity of the Cd 2+ complex, establishing the Cd 2+ -specific probe TriMeOBAPTQ ( N, N, N ′, N ′-tetrakis(5, 6, 7-trimethoxy-2-quinolylmethyl)-1, 2-bis(2-aminophenoxy)ethane). In contrast, TriMeOEGTQ ( N, N, N ′, N ′-tetrakis(5, 6, 7-trimethoxy-2-quinolylmethyl)-1, 2-bis(2-aminoethoxy)ethane) maintains a poor Cd 2+ /Zn 2+ selectivity in its fluorescence response. Although the crystal structures of Cd 2+ /Zn 2+ complexes with EGTQ and BAPTQ derivatives reveal the formation of multiple components including mononuclear and dinuclear complexes, the dinuclear Cd 2+ and Zn 2+ complexes with a linearly extended structure are regarded as possible fluorescent species in the solution. The conformational restriction of BAPTQ due to the orthophenylene moieties in the molecular skeleton is responsible for the formation of the weakly fluorescent, OH-bridged dizinc complex, which is critical to the strict Cd 2+ -specificity in the fluorescence response of TriMeOBAPTQ.